A brief history of the paradox : philosophy and the labyrinths of the mind - Sorensen, Roy A. (Oxford University Press, 2003)
Covers the entire history of philosophy, from the Greeks, through the Middle Ages, the Enlightenment, and the twentieth century, showing how individual philosophers have each grappled with a particular paradox.